Chromatography of Antihemophilic Factor on Diaminoalkane- and Aminoalkane-Derivatized Sepharose - Morgenthaler, J-J (Thrombosis and Haemostasis, 1982)
Antihemophilic factor was chromatographed on a homologous series of diaminoalkane- and aminoalkane-modified Sepharose beads. Both factor VIII procoagulant activity (VIII:C) and protein are retarded on these columns when compared to their elution on a column made of unmodified Sepharose. Longer chains bind VIII:C and protein more tightly than shorter chains. No bound activity could be eluted with ethylene glycol. Increasing ionic strength eluted VIII:C and protein from aminoalkane- as well as from alkane-Sepharose. It seems likely that hydrophobic, rather than ionic forces, are responsible for the binding of VIII:C to the latter carriers.
Keywords: Factor VIII; von Willebrand factor; Modified Sepharose; (Hydrophobic interaction) chromatography